Development of a Smart Road Divider Mechanism for Ambulance Path Clearance in Urban Traffic - Javeriya; Dr. Mohammed Abdul Waheed; Saniya Farheen (Utilitas Mathematica, 2025)
Urban traffic congestion remains one of the primary challenges in ensuring rapid and uninterrupted movement of emergency vehicles, particularly ambulances. Delays in such scenarios can often lead to life-threatening consequences. To address this issue, this paper presents the design and development of a Smart Road Divider Mechanism that dynamically reconfigures traffic lanes in real-time to provide a clear path for ambulances. The system is built using Arduino Uno as the core controller, integrated with RF modules for wireless communication between the ambulance unit and the traffic unit. Upon receiving a signal from the approaching ambulance via an RF transmitter, the traffic-side RF receiver activates a motorized movable divider, guided by infrared (IR) sensors and a DC motor driver, to create a dedicated emergency lane. LED indicators provide real-time visual cues to other vehicles. The prototype was tested under controlled conditions and demonstrated effective response times and reliable communication, showcasing its potential for urban deployment. This approach offers a low-cost, automated solution to improve emergency response infrastructure in smart city environments.